Political regionalism: devolution, Metropolitanization and the right to decide - Calzada, I (Edward Elgar Publishing, 2018)
This chapter examines how a new political regionalism pattern characterised by devolution and self-determination claims expressed and embodied via geo-democratic practices such as the ‘right to decide’ is emerging in three small, stateless and cityregional nations in Europe: Scotland, Catalonia and the Basque Country. Three main arguments are presented as the source of such diverse and pervasive city-regional ‘metropolitanisation’ processes: geo-economics, geo-politics and geo-democratics. This chapter posits that from the political regionalism perspective, geo-economic arguments claiming devolving powers are important, but in the event of being allowed the ability to hold a referendum by nation-states, however likely or unlikely, geo-political and geodemocratic manifestations count even more. Ultimately, is the ‘right to decide’ a potential ‘democratic’ extension of the ‘right to the city’? Insofar as these three small stateless nations are advocating a ‘civic nationalism’ appealing to ‘European’ values, the chapter concludes by exploring how devolution claims could increasingly ‘Europeanize’ the political regional agenda, in an ongoing push and pull of having ‘more say’ in the EU, fuelled by an increasing metropolitan drive and a bottom-up democratic experimentation towards the ‘right to decide’.